Analisis Pengaruh Makroekonomi Terhadap Capital Adequency Ratio (CAR) pada Bank Konvensional yang Terdaftar di BEI pada Periode 2020-2024 - Risalatul Mu’awanah; Maretha Ika Prajawati (Jurnal Manajemen Bisnis Digital Terkini, 2025)
Banking stability plays a crucial role in maintaining financial system resilience and supporting national economic growth. Fluctuations in macroeconomic factors often impact banks' financial health, particularly their capital. This study aims to explore how macroeconomic factors such as inflation, central bank benchmark interest rates, and gross domestic product (GDP) impact capital adequacy ratio (CAR) in conventional banks listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. This study employed a quantitative approach with an associative design, utilizing secondary data. The sample size for this study was 43 conventional banks. Data analysis was performed using multiple linear regression using SPSS. The findings indicate that inflation and benchmark interest rates do not significantly impact financial health, while GDP indicators show a modest positive trend. These findings confirm that macroeconomic conditions are not yet a dominant factor in determining bank capital adequacy. Therefore, it is suspected that internal factors such as risk management, profitability, and operational efficiency play a greater role in maintaining bank capital stability.